Extracting inflation expectations and inflation risk premia from the term structure: A joint model of the UK nominal and real yield curves - Joyce, Michael A.S.; Lildholdt, Peter; Sorensen, Steffen (Journal of Banking & Finance, 2010)
This paper analyses the UK interest rate term structure over the period since October 1992, when the United Kingdom adopted an explicit inflation target, using an affine term structure model estimated using both government bond yields and survey data. The model imposes no-arbitrage restrictions across nominal and real yields, which enables interest rates to be decomposed into expected real policy rates, expected inflation, real term premia and inflation risk premia. The model is used to shed light on major developments over the period, including the impact of Bank of England independence and the low real bond yield ‘conundrum’.